2017
DOI: 10.1002/asia.201700472
|View full text |Cite
|
Sign up to set email alerts
|

Diketopyrrolopyrrole‐Porphyrin Based Conjugated Polymers for Ambipolar Field‐Effect Transistors

Abstract: Porphyrin-based molecules have been widely used in dye-sensitized solar cells and bulk heterojunction solar cells, but their application in field-effect transistors (FETs) is limited. In this work, two conjugated polymers based on diketopyrrolopyrrole and porphyrin units were developed for FETs. The polymers exhibit extra-low band gap with energy levels close to -4.0 eV and -5.0 eV due to the strong electron-donating and withdrawing ability of porphyrin and diketopyrrolopyrrole. With additionally high crystall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…four meso and eight β -coordination sites) in Por-based materials is also a benefit to efficient functionalization by finely tuning the electronical, optical and photochemical properties through molecular level design. 16 Por-based materials are widely used in dye-sensitized solar cells (DSSCs), 17 sensors, 18 and field effect transistors (FETs) manufacturing, 19 etc. According to recent research, 20 metalloporphyrins (MPors) derivatives are potential materials for both photochemical and photoelectrochemical reduction of CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…four meso and eight β -coordination sites) in Por-based materials is also a benefit to efficient functionalization by finely tuning the electronical, optical and photochemical properties through molecular level design. 16 Por-based materials are widely used in dye-sensitized solar cells (DSSCs), 17 sensors, 18 and field effect transistors (FETs) manufacturing, 19 etc. According to recent research, 20 metalloporphyrins (MPors) derivatives are potential materials for both photochemical and photoelectrochemical reduction of CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Since the donor–acceptor (D:A) bulk-heterojunction (BHJ) concept was applied into organic solar cells (OSCs), , tremendous progress has been made in developing both novel materials and photovoltaic devices. Initially, fullerene derivatives are the dominant electron acceptors in OSCs, but their narrow absorption bands and deep energy levels are difficult to be modified, resulting in the limited application in OSCs. Recently, non-fullerene electron acceptors with tunable chemical structures have made rapid progress, in which the power conversion efficiencies (PCEs) have exceeded 14% in single-junction cells and 17% in tandem cells. The PCEs in non-fullerene organic solar cells (NFOSCs) are much better than those of fullerene-based solar cells, also indicating their great potential application in large-area devices. Efficiency, stability, and cost are the three key issues for OSCs’ industry application, in which it is still a big challenge to simultaneously realize high efficiency and excellent stability in one cell. , Therefore, it is an important task to improve the stability in these high performance NFOSCs, from new materials design and new devices configuration.…”
Section: Introductionmentioning
confidence: 99%
“…Porphyrin derivatives have unique optical and electronic properties because of their 18 delocalized π-electrons . In addition, the absorption of porphyrins lies in both the blue (Soret band) and red (Q band) parts of the visible spectrum and can be easily extended into the NIR region by using the donor–acceptor design. These properties enable porphyrins to be successfully applied in photovoltaic devices, such as dye-sensitized solar cells with PCEs over 13%. , Porphyrin-based semiconductors have also been widely reported as electron donors in OSCs and obtained impressing PCEs, , but these materials have been rarely used as electron acceptors. In our previous work, a new star-shape porphyrin-based electron acceptor has been successfully developed, and a promising PCE of 7.4% was obtained . The result indicated that porphyrin has a great potential to build new non-fullerene acceptors for high-performance OSCs.…”
Section: Introductionmentioning
confidence: 99%